2019
DOI: 10.1148/rg.2019180087
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy CT in Evaluation of the Acute Abdomen

Abstract: Evaluation of the nontraumatic acute abdomen with multidetector CT has long been accepted and validated as the reference standard in the acute setting. Dual-energy CT has emerged as a promising tool, with multiple clinical applications in abdominal imaging already demonstrated. With its ability to allow characterization of materials on the basis of their differential attenuation when imaged at two different energy levels, dual-energy CT can help identify the composition of internal body constituents. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 84 publications
0
58
0
1
Order By: Relevance
“…They found that the addition of unenhanced images increased the Youden index from 0.41 to 0.58 for one observer and from 0.42 to 0.61 for the other. Dualenergy CT is a recent technical improvement for assessing acute abdominal conditions (25). Dual-energy CT characterizes materials based on their differential attenuation when imaged at two different energy levels.…”
Section: Predicting the Best Treatment Strategymentioning
confidence: 99%
See 3 more Smart Citations
“…They found that the addition of unenhanced images increased the Youden index from 0.41 to 0.58 for one observer and from 0.42 to 0.61 for the other. Dualenergy CT is a recent technical improvement for assessing acute abdominal conditions (25). Dual-energy CT characterizes materials based on their differential attenuation when imaged at two different energy levels.…”
Section: Predicting the Best Treatment Strategymentioning
confidence: 99%
“…Thus, dual-energy CT can help identify the composition of materials inside the body. In patients with SBO, dual-energy CT may be able to help determine whether a high-attenuation area contains iodine (ie, is enhancing) or, instead, hemoglobin degradation products (Fig 2) (25). Dualenergy CT can provide virtual unenhanced images, thereby obviating an unenhanced acquisition (25).…”
Section: Predicting the Best Treatment Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…ist in einer kürzlich durchgeführten Umfrage der Arbeitsgemeinschaft Gastrointestinal-und Abdominaldiagnostik der Deutschen Röntgengesellschaft gezeigt worden [6]. Der potenzielle Zugewinn der neusten CT-Weiterentwicklung in Form der Dual-Energy-CT (DECT) ist vielversprechend und Gegenstand aktueller Untersuchungen [7].…”
Section: Aktueller Wissensstandunclassified